Case Report: Effective Treatment With Pyrotinib and Capecitabine in a Heavily Pretreated Locally Advanced Breast Cancer Harboring Both HER2 Overexpression and Mutant - Gao, Zhichao; Xu, Junnan; Wang, Yan; Wu, Jie; Sun, Tao (Frontiers in Oncology, 2021)
The prognosis for female patients with locally advanced breast cancer (LABC) has improved with the emergence of novel drugs, especially for those who have HER2 overexpression or ERBB-2 amplification. Trastuzumab-based regimen has been the paradigm in guidelines as first-line therapy, whereas many patients got progressive disease after several cycles of treatment or rapidly progress because of primary resistance. Point mutations of ERBB2 gene occur in both HER2-amplication and non-amplification patients, with a 2% ratio in HER2 non-amplification cohort and 1.48% in HER2 amplication population. The acquired mutation ratio of ERBB2 substantially raised to 16.7%–17.7% in patients prior to trastuzumab treatment. ERBB2 mutation may be a critical reason of resistance and disease progression among the patients treated with anti-HER2 monoclonal trastuzumab or dual anti-HER2 antibodies with trastuzumab and pertuzumab, or tyrosine-kinase inhibitor. ERBB-2 mutation with L755S and V842I indicates resistance to trastuzumab, while that with L755S and K753I indicates resistance to lapatinib; these mutations maybe sensitive to pan-HER tyrosine-kinase inhibitors. A 48-year woman diagnosed with HER2-positive LABC developed trastuzumab resistance after three lines of trastuzumab cross-line treatment with partial response (PR) as the best response. The tissue was performed by next-generation sequencing (NGS), and the results discovered L755S in ERBB2 gene. Then, she received effective treatment with pyrotinib plus capecitabine and underwent mastectomy after six cycles of combined treatment with PR. Subsequently, breast mastectomy was performed, and she took pyrotinib plus capecitabine for 1 year and pyrotinib monotherapy for another 1 year as adjuvant therapy and achieved a long-term clinical benefit. In conclusion, pyrotinib is a potential neoadjuvant agent for patients who are heavily pretreated and harbor both ERBB2 amplification and ERBB2 mutant in locally advanced breast cancer.